The Pattern of Educational System Participation in the Development of Elite Sports - Sattari, Mehri; Mohammadpour Yaghini, Habib; Najafzadeh, Mohammad Rahim; Najafzadeh, Farrokhlaqa (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study was conducted with the aim of presenting a model for the participation of the educational system in the development of elite sports. Methods and Materials: The present research is applied in nature and employs a qualitative method for data collection. The statistical sample of this research consisted of 22 experts and specialists in physical education, officials from the physical education departments of the Ministry of Education, deputies and physical education and health experts from provincial centers, as well as directors and deputies from the elite sports department of the Ministry of Sports and Youth across the provinces. The sampling process was purposeful and continued until data saturation was achieved. Data collection was carried out through semi-structured in-depth interviews. The data obtained from the interviews were analyzed using open, axial, and selective coding processes, and the components of the qualitative model (grounded theory), including the main category, causal conditions, intervening conditions, context, strategy, and outcomes, were identified. The final model was presented based on the Strauss and Corbin''s paradigmatic model. Findings: The results indicated that based on the axial coding and common concepts between the categories under study, 15 major categories were extracted. These categories included interaction with non-sports organizations, interaction with sports organizations, economic factors and financial supporters, human resources, sports equipment, sports facilities, managerial factors, development of principled curricula, implementation of appropriate evaluation systems, the role of the family, organizing sports events, attention to extracurricular programs in schools, use of media, the role of teachers and school administrators, and individual factors for the development of elite sports. Conclusion: Based on the findings of this study, the educational system can contribute to the development of elite sports in the country through categories such as interaction with non-sports organizations, interaction with sports organizations, economic factors and financial supporters, human resources, securing sports equipment for elite sports development, sports facilities, managerial factors, development of principled curricula, implementation of appropriate evaluation systems, the role of the family, organizing sports events for talent development, attention to extracurricular programs in schools, use of media, the role of teachers and school administrators, and individual factors.